Tanggung Jawab Perusahaan Jasa Transportasi Online Terhadap Mitra Kerja Yang Terkena Risiko Ditinjau Dari Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan Dan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja (Studi Di Kota Mataram) - Dian Sri Wahyuni; Any Suryani Hamzah; Rahmawati Kusuma (Fakultas Hukum Universitas Mataram, 2023)
This study aims to determine the responsibilities of online transportation service companies to partners exposed to risk in terms of Law Number 13 of 2003 concerning Employment and Law Number 11 of 2020 concerning Job Creation and the factors that affect the responsibility of transportation service companies online to partners. This research uses conceptual, legislation, and sociological approaches to normative-empirical law. In contrast, the data collection techniques used in this study were library materials and interviews. The study results show that the company provides an alternative in the form of insurance to partners as a form of concern for the company. And the factors that affect the responsibility of the company with the driver are the non-fulfilment of the elements of the working relationship because the company's relationship with the driver is only a partnership relationship.